Percepção de estresse e recuperação, variabilidade da frequência cardíaca e tempo de reação de atletas de futebol de alto rendimento em diferentes períodos de treinamento - Felipe de Oliveira Matos (2010)
In soccer are notorious psychophysical requirements imposed on players in search of the best sports results. These requirements are derived mainly from high loads of training and a very long competition calendar, which increases the need for continued high levels of performance for extended periods of time, making the physical and psychological recovery of athletes difficult. The imbalance between the stress resulting from demands sports (training and competition) and their proper rehabilitation may entail negative effects such as reduced performance and overtraining. Therefore, the objective of this study was to investigate the behavior of psychophysiological variables, indicators of possible states of stress and recovery in soccer players throughout the season sports and correlate them with the training loads. To this, 17 soccer players (18.4 ± 0.6 years, 9.64 ± 1.61% fat and VO2max 49.46 ± 2.88 ml / kg / min.) Of a junior team Brazil's national first division. We monitored the perception of stress and recovery through the questionnaire RESTQ-Sport, the heart rate variability (HRV), analyzed in the domain of time and frequency through the records of the RR intervals at rest, and simple reaction time. We conducted three collections of data, a control at baseline (C), after four weeks of intense training (T1) and one after four weeks of light training (T2) performed after T1. The training loads were quantified by means of pulses of training. We did not find significant differences in any of the scales of perception of stress and recovery and HRV in these three collections. The simple reaction time showed a significant increase (p = 0.016) at T1 in relation to C. Regarding the training loads, they showed significant negative correlations (p <0.05) with the indices of HRV (SD HR, SDNN and VLF_%) at T1 and T2 in the index VLF_Hz. The results indicate that the reaction time was the most sensitive to changes in training loads and HRV values that are related to these changes.